Thomas Kuhn's Quasi-Fideism - Marré, Thomas (Heythrop journal, 2024)
Abstract: I argue that Kuhn's account of scientific practice is profitably understood as a kind of hinge epistemology: like our epistemic practices more generally, scientific inquiry is made possible precisely by the fact that certain things are not subject to doubt. In Kuhn's own words, ‘dogmatism’ is essential to scientific practice and one of the primary engines of its success. For this reason, I argue that Kuhn's account is a rich source for reflection on the relationship between faith and reason. At the same time, Kuhn has faced objections similar to those which have faced hinge-epistemologists: how can disputes grounded in different, incompatible ‘dogmas’ be rationally resolved? Kuhn's response is similar to one put forward by Duncan Pritchard, but is, I argue, an improvement on it. In particular, the hinges on which deep scientific disagreement turns are for Kuhn certain shared values in light of which debate is possible. The choice among competing dogmas can, I argue, be understood on analogy with a prudential judgement of practical reasoning, i.e., an exercise of phronēsis.